ANALYSIS OF ONOBRYCHIS GENETIC DIVERSITY USING SSR MARKERS FROM RELATED LEGUME SPECIES - S. Avcı; E. Ilhan; M. Erayman; C. Sancak (Journal of Animal and Plant Sciences, 2014)
Availability of legume microsatellite markers for Onobrychis taxa was limited. However, cross genera utilization of such markers has been of great interest due to the high cost and labor. In the present study, we attempted to transfer microsatellite markers from Phaseolus vulgaris L. and Medicago truncatula Gaertn. to Onobrychis genus. Additionally, transferred markers were used to identify genetic diversity among Onobrychis taxa collected from different regions of Turkey. Of the 95 SSR primer pairs previously used for P. vulgaris and M. truncatula, 18 primers were successfully amplified and showed polymorphism among 58 Onobrychis taxa. Eighteen SSR primers observed 79 loci resulting in 725 alleles. The highest number of loci was obtained from BM175 and MTIC84 primers. Gene diversity and polymorphism information content values showed that P. vulgaris primers produced the most informative loci on Onobrychis genomes. The highest genetic diversity values were obtained for Onobrychis argyrea Boiss. subsp argyrea Boiss. (53)while the lowest fromOnobrychis cornuta (L.) Desv.(1). The average diversity values were the highest on Hymenobrychis section which was followed by Heliobrychis, Onobrychis, Laphobrychis and Dendobrychis sections. Magnitude of genetic variation was the highest within Onobrychis section in which genetic similarity values ranged from 0.013 to 0.399. The SSR and phylogenetic analysis results showed that sections were separated similar to their morphological characteristics. However, Hymenobrychis and Heliobrychis clearly separated from other sections. Our study showed that Onobrychis genomes could be successfully studied using other legume SSR markers. Therefore, they can be used for conservation of Onobrychis species as well as improving new varieties for feed use.
Keywords: Onobrychis; SSR transferability; Medicago truncatula; Phaseolus vulgaris